KRITIK SOSIAL DALAM NOVEL ORANG-ORANG BIASA KARYA ANDREA HIRATA - Agus Yulianto (tuahtalino, 2021)
The purpose of this study is to find out the forms of social criticism contained in the novel Orang-Orang Biasa by Andrea Hirata. The problem in this research is how the forms of social criticism contained in the novel Orang-Orang Biasa by Andrea Hirata. This research uses a descriptive qualitative method by using the sociology of literature approach. Based on the results of the analysis it can be seen that the forms of social criticism contained in this novel are: 1. economic criticism; 2. criticism of the rise of crime; and 3. criticism of education.